The Ecological Transition from the Perspective of the Poor - Frédéric-Marie Le Méhauté (Religions, 2023)
In the last few years, a theological trend has developed in France that is committed to listening to the words of people in precarious situations. In the tradition of Father Joseph Wresinski, founder of ATD Fourth World, this theological movement seeks to hear the joys, the struggles, the hopes, the dreams, and the faith of those who live on the margins of the world. They are the first to be affected by social and environmental injustices. They are the first to fight poverty. They are the first to invent a sustainable way of life. Listening to and taking seriously the experiences and words of the very poor opens up new perspectives for theology, especially in the ecological field. Indeed, the link between the cry of the earth and the cry of the poor has become commonplace. According to the World Bank, it is even “evidence”. Certainly “everything is linked”, as Pope Francis writes in Laudato Si’, but the characterization of this link must be deepened. It is not simply a matter of juxtaposing these two cries, but of perceiving that it is only from the most excluded that fair, effective, and sustainable solutions can be proposed. Bringing their words and thoughts into our modern agoras is an essential anthropological, political, and theological challenge for ecological conversion.